2007
DOI: 10.1111/j.1365-2842.2007.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Precision of in vivo spectrophotometric colour evaluation of natural teeth

Abstract: The aim of the study was to evaluate the precision of a reflectance spectrophotometer during longitudinal assessment of tooth colour in vivo. The spectrophotometric data of five standardized circular areas on the labial surfaces of six teeth (four upper and two lower), from 22 dental students, were recorded on three separate days (1st, 3rd and 30th) employing a repeated-measuring design (n = 3). Total colour differences were calculated according to the equation DeltaEpsilon = [(DeltaL*)(2) + (Deltaa*)(2) + (De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 38 publications
(62 reference statements)
1
59
0
15
Order By: Relevance
“…The perceptible threshold level of ∆E* values was set at 1 and the acceptable threshold level of ∆E* was set at 3.7 (4,5,8,9,16). Thus, color changes below or above the value of ∆E* = 3.7 were determined as 'acceptable' or 'unacceptable' , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The perceptible threshold level of ∆E* values was set at 1 and the acceptable threshold level of ∆E* was set at 3.7 (4,5,8,9,16). Thus, color changes below or above the value of ∆E* = 3.7 were determined as 'acceptable' or 'unacceptable' , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Such color measuring devices (CMDs) eliminate the subjectivity related to color determination and increase the level of consistency in the color determination process. 3,[5][6][7] Henceforth, CMDs can be beneficial for the process of shade determination.…”
Section: Introductionmentioning
confidence: 99%
“…Every curve is unique for each sample. 13 Several studies [23][24][25] have shown that spectrophotometry is a reliable, reproducible, accurate, and quantitative method.…”
Section: Introductionmentioning
confidence: 99%